2017
DOI: 10.1139/cjpp-2016-0667
|View full text |Cite
|
Sign up to set email alerts
|

Lingonberry anthocyanins protect cardiac cells from oxidative-stress-induced apoptosis

Abstract: Lingonberry grown in northern Manitoba, Canada, contains exceptionally high levels of anthocyanins and other polyphenols. Previous studies from our lab have shown that lingonberry anthocyanins can protect H9c2 cells from ischemia-reperfusion injury and anthocyanin-rich diets have been shown to be associated with decreased cardiovascular disease and mortality. Oxidative stress can impair function and trigger apoptosis in cardiomyocytes. This study investigated the protective effects of physiologically relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…Anthocyanins have been found with beneficial effects on obesity and diabetes control, cardiovascular disease and cancer prevention, and visual and brain function improvement (Tsuda, 2012 ; Hannum, 2004 ). Mechanistically, the beneficial effect of anthocyanins on cardiovascular health include working as an antiplatelet agent in atherosclerosis and other CVD prevention, inducing nitric oxide formation in vessel thereby enhancing vasorelaxation, protecting cardiac cells from oxidative-stress-induced apoptosis, and increasing HDL cholesterol as well (Gaiz et al, 2018 ; Stoclet et al, 1999 ; Hassellund et al, 2013 ; Isaak et al, 2017 ).…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Anthocyanins have been found with beneficial effects on obesity and diabetes control, cardiovascular disease and cancer prevention, and visual and brain function improvement (Tsuda, 2012 ; Hannum, 2004 ). Mechanistically, the beneficial effect of anthocyanins on cardiovascular health include working as an antiplatelet agent in atherosclerosis and other CVD prevention, inducing nitric oxide formation in vessel thereby enhancing vasorelaxation, protecting cardiac cells from oxidative-stress-induced apoptosis, and increasing HDL cholesterol as well (Gaiz et al, 2018 ; Stoclet et al, 1999 ; Hassellund et al, 2013 ; Isaak et al, 2017 ).…”
Section: Anthocyaninsmentioning
confidence: 99%
“…Delphinidin has been revealed as the most active scavenger against superoxide anion [ 41 ]. Furthermore various reports have shown that anthocyanin has protective effects against oxidative stress in cell lines [ 42 , 43 , 44 ]. Several studies have also demonstrated the antioxidant functions of anthocyanins in vivo.…”
Section: Biological Functions Of Anthocyaninsmentioning
confidence: 99%
“…Cyanidin is one of the most prevailing anthocyanidins and a major pigment in berries, grapes and purple-coloured vegetables ( Wallace and Giusti 2015 ; Khoo et al., 2017 ). The studies on anthocyanins deal mainly with their chemoprotective action owed to the antioxidant capacity which is conferred by the anthocyanidin moiety ( Tedesco et al., 2001 ; Heo and Lee 2005 ; Isaak et al., 2017 ) and it is widely believed that the toxicity of anthocyanins is very low ( Wallace and Giusti 2015 ). Studies on the potential toxicity of anthocyanins/anthocyanidins are less represented, although some alarm has been triggered concerning their role in the so called ‘antioxidative stress’, which can be correlated with overconsumption of natural antioxidants, either in complex mixtures or as single isolated compounds ( Poljsak and Milisav 2012 ; Kwee 2014 ; Cai et al., 2018 ; Cásedas et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%